2010
DOI: 10.1007/s00894-010-0907-1
|View full text |Cite
|
Sign up to set email alerts
|

Structural studies of biologically active glycosylated polyamidoamine (PAMAM) dendrimers

Abstract: The partial modification of carboxylic acid terminated polyamidoamine (PAMAM) dendrimers with glucosamine has been reported to give dendrimer glucosamine conjugates novel immuno-modulatory and anti-angiogenic properties. Experimental analysis of these glycosylated dendrimers showed that, on average, eight glucosamine molecules were covalently bound to each dendrimer. In order to better understand the surface loading and distribution of these glucosamine molecules, molecular reactivity was determined by eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 18 publications
1
22
0
Order By: Relevance
“…We found that the overall negative charge of the unmodified dendrimer's surface [7], [8] did not favour interactions with the negatively charged surface residues Glu92, Asp99 and Asp101 that line MD-2's hydrophobic pocket. This is the most likely explanation for the lack of biological activity of the unmodified dendrimer.…”
Section: Resultsmentioning
confidence: 81%
See 4 more Smart Citations
“…We found that the overall negative charge of the unmodified dendrimer's surface [7], [8] did not favour interactions with the negatively charged surface residues Glu92, Asp99 and Asp101 that line MD-2's hydrophobic pocket. This is the most likely explanation for the lack of biological activity of the unmodified dendrimer.…”
Section: Resultsmentioning
confidence: 81%
“…Our previous modelling studies suggested that a dendritic architecture was important for this molecule's biological activity [7], [8]. In addition, our previous biological studies [6] were preceded by unpublished observations with smaller generations of partially glycosylated PAMAM dendrimers; these molecules did not have the desired biological activity.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations